Arm activity measure (ArmA): psychometric evaluation of the Swedish version - Therese Ramström; Lina Bunketorp-Käll; Johanna Wangdell (SpringerOpen, 2021)
Abstract Background Patient Reported Outcomes Measure (PROM) are commonly used in research and essential to understand the patient experience when receiving treatment. Arm Activity Measure (ArmA) is a valid and reliable self-report questionnaire for assessing passive (section A) and active (section B) real-life arm function in patients with disabling spasticity. The original English version of ArmA has been psychometrically tested and translated into Thai. Aims Translate and cross-culturally adapt ArmA to Swedish language and context. Further, to evaluate the reliability, validity and sensitivity of the Swedish version of the questionnaire (ArmA-S) in patients with disabling upper limb spasticity caused by injuries to the central nervous system (CNS). Materials and methods ArmA was translated and cross-culturally adapted according to established guidelines. Validity and reliability were evaluated in 61 patients with disabling spasticity. Face and content validity was evaluated by expert opinions from clinicians and feedback from patients with upper limb spasticity. Internal consistency reliability was assessed with Cronbach's alpha and test-retest reliability was assessed using the quadratic weighted kappa. Results ArmA-S was shown to be clinically feasible, with good face and content validity and no floor or ceiling effects. Internal consistency of ArmA-S was high and equivalent to ArmA; with Chronbach´s alpha coefficients values of 0.94 and 0.93 for section A and B, respectively. Test-retest reliability was good, with kappa values of 0.86 and 0.83 for section A and B, respectively. Some layout modifications of ArmA-S were made to further increase the user-friendliness, test-retest reliability, and responsiveness. Conclusion ArmA-S was shown to be a reliable and valid self-report questionnaire for use in clinical practice and research to assess improvements in passive and active upper limb function in patients with disabling spasticity.